TINGKAT PERCAYA DIRI ANAK USIA 5-6 TAHUN DI RA DARUSSA’ADAH DOMASAN - Raras Amalia Cantika Siwi (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2022)
Abstract: The purpose of this study was to describe the level of self-confidence of children aged 5-6 years at RA Darussa'adah Domasan. The method used in this research is descriptive qualitative by describing the confidence level of children aged 5-6 years in RA Darusssa'adah Domasan. There are two research subjects where parents and teachers are the informants. Data collection techniques used are interviews and observation. For this reason, the researcher carried out four stages to collect data related to the research subject. First, the researcher compiled a list of questions as an interview guide. Second, conduct interview sessions with informants. Third, make observations in the field and take notes. Fourth, the researcher presents the data obtained from data collection activities. The results showed that the level of self-confidence of children aged 5-6 years in RA Darussa'adah was at a moderate level and still needed motivation and support to develop it.